Distinct host-mycobacterial pathogen interactions between resistant adult and tolerant tadpole life stages of Xenopus laevis - Rhoo, Kun Hyoe (J Immunol, 2019)
Mycobacterium marinum (Mm) is a promiscuous pathogen infecting many vertebrates including humans, whose persistent infections are problematic for aquaculture and public health. Among unsettled aspects of host-pathogen interactions, the respective roles of conventional and innate-like (i)T cells in host defenses against Mm remain unclear. Here, we developed an infection model system in the amphibian Xenopus laevis to study host responses to Mm at two distinct life stages, tadpole and adult. Adult frogs possess efficient conventional T cell-mediated immunity, whereas tadpoles predominantly rely on innate-like (i)T cells. We hypothesized that tadpoles are more susceptible and elicit weaker immune responses to Mm than adults. However, our results show that although anti-Mm immune responses between tadpoles and adults are different, tadpoles are as resistant to Mm inoculation as adult frogs. Mm inoculation triggered a robust pro-inflammatory CD8(+) T cell response in adults, whereas tadpoles elicited only a non-inflammatory CD8 negative- and iT cell-mediated response. Furthermore, adult anti-Mm responses induced active granuloma formation with abundant T cell infiltration and associated with significantly reduced Mm loads. This is reminiscent of local CD8(+) T cell response in lung granulomas of human tuberculosis patients. In contrast, tadpoles rarely exhibited granulomas and tolerated persistent Mm accumulation. Gene expression profiling confirmed poor tadpole CD8(+) T cell response contrasting with the marked increase in transcript levels of the anti-Mm iT cell receptor rearrangement (iVα45-Jα1.14) and of CD4. These data provide novel insights into the critical roles of iT cells in vertebrate anti-mycobacterial immune response and tolerance to pathogens.